Urgensi Pendidikan Bahasa Arab untuk Anak-Anak : Investasi Cerdas untuk Masa Depan - A. Mairi Kurniadi (Journal on Education, 2024)
Arabic is one of the languages that plays an important role in the world, especially in the context of Islam and Middle Eastern culture. Early education in Arabic provides many benefits for children, including the strengthening of cultural identity, a deeper understanding of religion, and multilingual abilities that can support their cognitive development. Moreover, mastering Arabic can help children build a better cross-cultural understanding, foster tolerance, and prepare them to face an increasingly diverse global society. This research also highlights the importance of interactive and enjoyable learning approaches in teaching Arabic to children, such as the use of visual media and language games. It is hoped that Arabic education can equip children with a strong linguistic foundation and various skills relevant to their future.